Digital Marketing Challenges: Damar Batik Jogja and Utilizing the Shopee, Tiktok, and Instagram Platforms - Lasera, Greis; Anjelika, Aviva; Ariantanto, Wimar; Lero, Stevani; Pratama, Dandi Yoga; Kusumawardhani, Ratih (PT Inovasi Pratama Internasional, 2024)
The large number of internet users in Indonesia is a major factor for UMKM Damar Batik business actors to utilize digital marketing to reach wider consumers. Damar Batik, as one of the prominent brands in batik products, needs to optimize its digital marketing strategy in order to compete in an increasingly competitive market. In this community service program, the focus is directed at utilizing digital marketing to build brand awareness for Damar Batik. The results of this service show that the use of digital marketing through social media, e-commerce, has great potential to build brand awareness for Damar Batik. The use of consistent slogans or messages can help shape public perception of Damar Batik as a strong brand rooted in local batik culture. Platforms such as shope, tiktok and Instagram and e-commerce are considered to play an important role in strengthening the position of the Damar Batik brand in the eyes of the public as an authentic batik brand that is relevant to the times.